Designing a Strategic Employee Performance Evaluation Model in Independent Institutions of the Government - Saeid Jafarinia; Akbar Hassanpoor; Yusef Vakili; Bahram Torabi (مدیریت بهره وری)
This research was designed and implemented with a practical purpose. Using a qualitative method, 11 experts and operational managers of IKEO were interviewed using targeted sampling and after analyzing the content of the interviews and organizational documents (Guide to the strategic management system of IKEO and its subordinate units and the third five-year strategic formulation directive of this organization) the conceptual model of the research was extracted. In the validation phase, the researcher-made questionnaire consisting of 42 items was studied, distributed and analyzed among 40 field and operational managers and experts of the organization. The results led to the design of the model of strategic evaluation of the performance of employees in non-governmental institutions, especially IKEO. This model has six main factors that include personal growth and development, effective relationships, attention to the interests of stakeholders, creativity, innovation, national concern and finally job productivity. All the dimensions and components of the proposed model for strategic evaluation of employee performance in non-government institutions were approved after the evaluation in the research validation stage. Due to the lack of a suitable model to evaluate the performance of employees in IKEO and the acknowledgement of its managers to the existing deficiency, the designed model with the dimensions, components and indicators mentioned in this research meets the needs of the studied organization.